2005
DOI: 10.1161/circulationaha.104.517144
|View full text |Cite
|
Sign up to set email alerts
|

Early Structural and Functional Changes of the Vasculature in HIV-Infected Children

Abstract: HIV infection in childhood is associated with adverse structural and functional vascular changes that are most pronounced in children exposed to PI therapy. Longitudinal studies are required to differentiate the relative impact of HIV disease and ART and to assess the potential for prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
119
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(137 citation statements)
references
References 24 publications
13
119
2
3
Order By: Relevance
“…In particular, vascular abnormalities were more pronounced in children exposed to PI therapy. These findings support a role for both HIV infection itself and ARV, above all PIs, in the pathogenesis of early vascular disease, especially in atherosclerosis [37].…”
Section: Vascular Dysfunction In Hiv-infected Childrensupporting
confidence: 68%
“…In particular, vascular abnormalities were more pronounced in children exposed to PI therapy. These findings support a role for both HIV infection itself and ARV, above all PIs, in the pathogenesis of early vascular disease, especially in atherosclerosis [37].…”
Section: Vascular Dysfunction In Hiv-infected Childrensupporting
confidence: 68%
“…Comparisons of different treatment exposure groups revealed that endothelial function was impaired by a mean of 3.6% (95% CI, 1.8 to 5.3; p<0.001) for children exposed to PIs compared with untreated children and by a mean of 1.8% (95% CI, 0.01 to 3.5; p=0.05) compared with non-PI-treated patients. This study demonstrates that structural and functional changes of the vasculature are already present during childhood in HIVinfected children and these changes were most pronounced in children receiving protease inhibitors, but were also observed in non-protease inhibitors treated and untreated children and the findings of the study support a role for both HIV infection itself and ART, particularly protease inhibitors, in the pathogenesis of early vascular disease, likely to be relevant to future clinical atherosclerosis [101]. Stein et al, recently, presented preliminary data from a prospective, randomized, multicenter substudy (A5152s) to evaluate the effects of antiretroviral therapy on endothelial function in treatment-naïve HIV infected individuals.…”
Section: Clinical Assessment Of Endothelium In Hiv Infectionsupporting
confidence: 53%
“…In order to determine the impact of HIV infection and antiretroviral therapy on markers of early vascular disease in children, Charakida et al [101] studied 83 HIV-infected children (56 had taken HAART, of whom 31 received a regimen containing protease inhibitors; 27 were never treated and a control group of 59 healthy children). Carotid intima-media thickness (IMT) and endothelial function were measured by brachial artery flow-mediated dilatation (FMD).…”
Section: Clinical Assessment Of Endothelium In Hiv Infectionmentioning
confidence: 99%
“…The main risk factors involved in the development of atherosclerotic cardiovascular disease in HIV-infected patients are dyslipidemia, body fat redistribution, insulin resistance, vascular inflammation, fibrinolysis disorder and the side effects of antiretroviral therapy [36][37][38]. Their association with the traditional risk factors increases the risk of precocious atherosclerotic disease.…”
Section: Cardiovascular Manifestationsmentioning
confidence: 99%